Hydrogen bonding and molecular orientation at the liquid–vapour interface of water. Issue 14 (26th February 2015) - Cipcigan, Flaviu S.; Sokhan, Vlad P.; Jones, Andrew P.; Crain, Jason; Martyna, Glenn J.
Abstract : We discover two hydrogen bonding motifs in liquid water and a related asymmetry linked with molecular orientation at its liquid–vapour interface. Abstract : We determine the molecular structure and orientation at the liquid–vapour interface of water using an electronically coarse grained model constructed to include all long-range electronic responses within Gaussian statistics. The model, fit to the properties of the isolated monomer and dimer, is sufficiently responsive to generate the temperature dependence of the surface tension from ambient conditions to the critical point. Acceptor hydrogen bonds are shown to be preferentially truncated at the free surface under ambient conditions and a related asymmetry in hydrogen bonding preference is identified in bulk water. We speculate that this bonding asymmetry in bulk water is the microscopic origin of the observed surface structure.